The effect of Mg concentration on the resistance of PVD Zn-Mg coatings to corrosion driven organic coating delamination - Geraint Williams (Corrosion Science, 2015)
Zn–Mg PVD coatings applied to steel substrates are investigated with respect to their resistance to corrosion-driven organic coating delamination by both cathodic and anodic mechanisms. An in-situ scanning Kelvin probe is employed to quantify delamination rates on model polyvinyl butyral coated surfaces and determine the underfilm potentials associated with the delamination corrosion cell. Measurable rates of cathodic disbondment are observed at Mg compositions of ≤5% w/w, but all other Zn–Mg coatings in the range 10–25% w/w resist delamination for periods of up to 48 h. However, Mg compositions of ≥12% w/w produce a susceptibility to coating failure by anodic undermining.